Flexural behaviour of hybrid fibre-reinforced polymer (FRP) matrix composites - Sudarisman (Curtin University, 2009)
The flexural behaviour of three different hybrid fibre-reinforced polymer (FRP) matrix composites, i.e. S2-glass/E-glass/epoxy, TR50S carbon/IM7 carbon/epoxy, and E-glass/TR50S carbon/epoxy hybrid FRP composites, has been investigated. The main objectives of this study were to: (i) improve the flexural properties of the parent composite materials, i.e. E-glass/epoxy and TR50S carbon fibre/epoxy composites, through substitution of stronger fibres, i.e. S2-glass and IM7 carbon fibres, for the fibres of the parent composite materials, and (ii) determine the optimum stacking configurations that produced the maximum increase in flexural properties of the resulting hybrid composites. In addition to these, two secondary objectives related to the preliminary investigation of determining the optimum stacking configurations have also been established. The two secondary objectives were to: (i) determine the optimum values of the processing parameters of the composites under investigation, and (ii) determine the compressive strength and compressive modulus of the parent materials.The investigation was carried out experimentally, thus data presented and analysed were obtained from laboratory work. Optimum values of five processing parameters, i.e. (i) the concentration of matrix precursor within the solvent solution utilised to wet the fibres, (ii) the compressive pressure applied during hotpress curing, (iii) the vacuum pressure of the atmosphere inside the curing chamber, (iv) the dwell time during hot-press curing, and (v) the holding temperature during hot-press curing, have been established. The criteria for determining the optimum values of these parameters were optimum fibre content, minimum void content, and optimum flexural properties. Compressive strength and compressive modulus of the parent composite materials have also been determined.Specimens were cut from flat composite plates using a diamond-tipped circular blade saw. The longitudinal edges of the specimens were carefully polished to remove any possible edge damage due to cutting. The composite plates were produced from preforms comprised of a number of glass fibre/epoxy prepregs, carbon fibre/epoxy prepregs or a combination of these. All the fabrication procedures were carried out using manual techniques. Whilst the compressive tests were conducted in accordance with the ASTM D3410-03 standard, flexural tests were carried out according to Procedure A of the ASTM D790-07 standard. Span-to depth ratios, S/d, of 16, 32, and 64 were selected for flexural testing in order to determine the minimum value of S/d required to ensure flexural failure rather than shear failure. Fibre and void contents were evaluated from optical micrograph images of the slices perpendicular to the fibre direction of the samples.It was concluded that the optimum values of the five processing parameters under investigations were: (i) epoxy concentration, C[subscript]e ~ 50 wt%, (ii) compressive pressure, p[subscript]c ~ 1.00 MPa, (iii) vacuum pressure, p[subscript]v ~ 0.035 MPa, (iv) dwell time, t ~ 30 minutes, and (v) holding temperature, T ~ 120 °C. Compressive tests revealed that the order of compressive strength for the parent composite materials were arranged as follows: S2-glass fibre/epoxy (476 MPa), E-glass fibre/epoxy (430 MPa), IM7 carbon fibre/epoxy (426 MPa), and TR50S carbon fibre/epoxy (384 MPa). The compressive modulus of these parent composite materials were found to be ordered as follows: IM7 carbon fibre/epoxy (67.9 GPa), TR50S carbon fibre/epoxy (61.8 GPa), S2-glass fibre/epoxy (45.1 GPa), and E-glass fibre/epoxy (32.9 GPa). After considering these compressive properties, three different hybrid combinations, as mentioned earlier, were manufactured and evaluated with the prepreg layers of the fibre composites possessing higher compressive strength being placed at the compressively loaded side of the flexural specimens.Shorter beam specimens (S/d = 16) of the three hybrid systems exhibited increased flexural strength as the amount of stronger fibre content was increased, but no hybrid effect was noted. The increase appeared to follow the rule of mixtures and this was attributed to their failure mode being shear failure. For beams tested at S/d = 32 and S/d = 64, the three hybrid systems demonstrated three different trends. The S2-glass fibre/E-glass fibre/epoxy hybrid system, where the S2-glass fibre (substituted at the compressive loading face) was slightly stronger and stiffer compared to the E-glass fibre at the tensile side, demonstrated increases in flexural strength together with the presence of a hybrid effect following partial substitution of the S2-glass fibre for E-glass fibres at the compressive side. The IM7 carbon fibre/TR50S carbon fibre/epoxy hybrid system, where the IM7 carbon fibre (substituted at the compressive side) was slightly stronger but significantly stiffer in compression compared to the TR50S fibre at the tensile side, exhibited a slight increase in flexural strength that appeared to obey the rule of mixtures.This result was attributed to the strength increase in the compressive side introduced by the substituted fibres not being sufficient to suppress the increase of internal compressive stress due to the increase in compressive modulus of the substituted fibres. The E-glass fibre/TR50S carbon fibre/epoxy hybrid system, where the E-glass fibre (substituted at the compressive side) was found to be slightly stronger but significantly less stiff in compression compared to the TR50S fibre at the tensile side, demonstrated a significant increase in flexural modulus and also exhibited a significant hybrid effect. The decrease in internal compressive stresses generated at the compressive side due to the decreased compressive modulus of the substituted fibre, when combined with the increase in compressive strength of the substituted fibre, was thought to led to the significant increase of flexural strength for this hybrid system.General trends observed in flexural modulus for the three hybrid systems were reasonably similar with any change in flexural modulus appearing to obey the rule of mixtures. Whilst an increase in flexural modulus was noted for higher contents of stronger fibre in the case of the S2-glass fibre/E-glass fibre/epoxy hybrid system and IM7 carbon fibre/TR50S carbon fibre/epoxy hybrid system, a decrease in flexural modulus with increased quantities of stronger fibre was exhibited by the E-glass fibre/TR50S carbon fibre/epoxy hybrid system. The increase or decrease in flexural modulus was attributed to the relative stiffness in compression of the substituted fibre when compared to that of the respective parent composite materials.Unlike the S2-glass fibre/E-glass fibre/epoxy hybrid system and IM7 carbon fibre/TR50S carbon fibre/epoxy hybrid system that did not exhibit any significant trend with regards the effect of the substitution of stronger fibre at the compressive side, the E-glass fibre/TR50S carbon fibre hybrid system demonstrated a significant increase in the energy stored to maximum stress with increasing content of the stronger fibre. This increase was mainly attributed to the increased strain–to-maximum stress of the hybrid system with respect to that of the parent composite material.In addition, for the three hybrid systems under investigation, the most significant change in flexural properties was noticed following substitution of the first layer at the compressive face. The relative position with respect to the neutral plane of the substituted layer was thought to be the reason for this phenomenon. It was also noted that flexural properties increased with the increase in S/d. A change in failure morphology was noted with the change of S/d from 16 to 32. It was thus determined that a S/d ratio of at least 32 was required in order to promote flexural failure (as opposed to shear failure). For the S2-glass fibre/E-glass fibre/epoxy hybrid system, this change appeared more obvious in comparison with that the other two hybrid systems with this change being accompanied by a significant increase in flexural strength.The main general conclusions that could be drawn from this investigation were that, although the flexural modulus appeared to obey the rule of mixture, an increase in flexural strength together with the presence of a hybrid effect, would most probably be observed when the fibre substituted at the compressive side possessed a significantly lower modulus combined with significantly higher compressive strength as demonstrated by the hybrid TR50S carbon - E-glass FRP composites. The most significant change in properties was exhibited by the first layer substitution whilst increasing the value of S/d resulted in an increase of flexural strength, with S/d = 32 being determined to be sufficient in order to promote flexural failure as opposed to shear failure.